The Effect of Tax Incentives and Tax Education on MSME Taxpayer Compliance During The Covid-19 Pandemic - Nur Sandi Marsuni (GoodWill, 2023)
Background: Micro, Small and Medium Enterprises (MSMEs) play a crucial role in the Indonesian economy by making a significant contribution to local and national economic growth. However, the main challenge facing MSMEs is low levels of tax compliance, which can hinder the government's ability to provide public services and infrastructure. Objective: This research aims to investigate the influence of tax awareness and tax socialization on taxpayer compliance in MSMEs. The main focus is to provide an in-depth understanding of the factors that influence tax compliance among MSMEs. Method: This research uses a literature study approach by collecting data from various sources such as books, journals and scientific articles that are relevant to the research topic. The analysis was carried out to identify main findings related to tax awareness, tax socialization, and tax compliance of MSME actors. Results: From the research results, it was found that tax awareness and tax socialization have a significant influence on the level of tax compliance of MSME actors. Effective tax outreach and increasing tax awareness can increase the willingness of MSMEs to fulfill their tax obligations better. Conclusion: This article concludes that the government needs to increase tax outreach efforts and tax awareness education among MSMEs as a strategy to increase tax compliance. These steps are expected to help overcome persistent tax compliance challenges in the MSME sector, which in turn will support sustainable economic growth and equitable economic development throughout Indonesia. Thus, this research makes an important contribution in understanding the dynamics of taxation in the MSME sector and provides a basis for more effective public policy in supporting the development of MSMEs in Indonesia.